Drug abuse : inside an American epidemic - Horning, Nicole (Hot topics (San Diego, Calif.), 2019)
Details the recent growth in drug abuse by people of all ages and examines the effects of drugs not only on the body, but on society as a whole as well. Also explores the modern "war on drugs" and discusses the decision by some states to legalize marijuana under certain restrictions.